THEORETICAL AND METHODOLOGICAL PRINCIPLES OF JUSTIFICATION OF THE CAREER MANAGEMENT ALGORITHM OF THE OFFICERS OF THE NATIONAL GUARD OF UKRAINE - Bielai, Serhii; Trobiuk, Volodymyr; Holovnia, Andriy (Honor and Law, 2023)
In the modern world, which is characterized by rapid changes in the geopolitical landscape, technologies and socio-economic conditions, the issue of adaptation of military structures, in particular in the aspect of career development of the officer ranks, is gaining special relevance. This becomes especially important in the context of the long war waged by the Russian Federation against Ukraine, so the career growth of officers gains both professional and strategic importance. In general, career development at the National Guard of Ukraine is a dynamic process that requires a holistic approach, including management selection, assessment, planning, skill development, adaptation to new conditions, and continuous self-improvement. This process not only contributes to the realization of individual career goals of officers, but also ensures the effective functioning and development of the military organization as a whole. The study identifies factors that affect the professional development of officers during the development of an algorithm for managing the career of the National Guard of Ukraine officer, and at the same time provide modern challenges and needs for the selection of managerial personnel. Particular attention is paid to establishing clear criteria that reflect the current level of officer professionalism. These include task execution, unit command and resource management, as well as the ability to innovate, think strategically and contribute to the development of the National Guard of Ukraine military system as a whole. The role of military-political changes in the formation of career paths of the National Guard of Ukraine officers is revealed. International conflicts, reforms of military structures, technological innovations and changes in military doctrine affect the requirements for officers and also open up new opportunities for career growth. In this context, there is a need to develop and implement an effective career management algorithm that takes into account these changing factors and stimulates continuous self-improvement and learning, which is key to ensuring an effective and flexible career development system at the National Guard of Ukraine. This approach allows not only to meet current management recruitment requirements, but also to predict future needs, adapt and ensure that the officer corps will be prepared to solve tasks both today and in the future. Further scientific research is needed in the areas of integration of the proposed career management algorithm into the practical activities of the National Guard of Ukraine, internal issues of updating educational programs and taking into account psychological aspects in career development, as well as the issue of selecting managerial personnel for the components of the security and defense sector of Ukraine.